2005
DOI: 10.1016/j.ccr.2004.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Role for the epidermal growth factor receptor in neurofibromatosis-related peripheral nerve tumorigenesis

Abstract: Benign neurofibromas and malignant peripheral nerve sheath tumors are serious complications of neurofibromatosis type 1. The epidermal growth factor receptor is not expressed by normal Schwann cells, yet is overexpressed in subpopulations of Nf1 mutant Schwann cells. We evaluated the role of EGFR in Schwann cell tumorigenesis. Expression of EGFR in transgenic mouse Schwann cells elicited features of neurofibromas: Schwann cell hyperplasia, excess collagen, mast cell accumulation, and progressive dissociation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 49 publications
9
131
0
1
Order By: Relevance
“…We believe that the Ctv-a mouse may also be a useful model for studies of the peripheral nervous system because the Cnp promoter also targets Schwann cells (Gravel et al, 1998). In a recently described transgenic mouse model of neurofibroma, expression of the human epidermal growth factor receptor (hEGFR) was directed to CNP-expressing Schwann cells (Ling et al, 2005). These mice developed Schwann cell hyperplasias but showed no signs of glioma development, which was explained by the lack of EGFR ligands in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the Ctv-a mouse may also be a useful model for studies of the peripheral nervous system because the Cnp promoter also targets Schwann cells (Gravel et al, 1998). In a recently described transgenic mouse model of neurofibroma, expression of the human epidermal growth factor receptor (hEGFR) was directed to CNP-expressing Schwann cells (Ling et al, 2005). These mice developed Schwann cell hyperplasias but showed no signs of glioma development, which was explained by the lack of EGFR ligands in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…98 Although the EGF receptor is in the same family as the NRG1 receptors, the phenotype of Cnp-hEGFR mice is more subtle than that of P 0 -GGFb3 mice. Cnp-hEGFR mice show Schwann cell hyperplasia, dissociation of Schwann cells from axons, increased numbers of intraneural mast cells, and fibrosis, but frank neurofibroma formation is rare, indicating that inappropriate expression of the EGF receptor is not sufficient for tumorigenesis.…”
Section: Currently Available Mouse Models Of Neurofibroma and Mpnst Pmentioning
confidence: 99%
“…The generation and characterization of the CNP-EGFP mouse has been previously described (Yuan et al, 2002) Details on the generation and characterization of the CNP-hEGFR transgenic mice have been previously reported (Ling et al, 2005). Genotyping of these transgenic mice was performed by PCR.…”
Section: Transgenic and Mutant Micementioning
confidence: 99%
“…We have recently utilized a CNP-hEGFR mouse, in which the human EGFR is overexpressed in neural progenitors that express the CNP gene (Ling et al, 2005;Aguirre et al, 2005;Aguirre et al, 2007). We showed that OPCs that express the membrane proteoglycan NG2 also display EGFR signaling .…”
Section: Introductionmentioning
confidence: 99%